PENGARUH STRATEGI OPERASI TERHADAP KEUNGGULAN OPERASIONAL UMKM KABUPATEN BANDUNG (STUDI KASUS PADA UMKM MAKANAN DAN MINUMAN DI KABUPATEN BANDUNG) - Andri Irawan; Eka Ludiya (Ultima Management : Jurnal Ilmu Manajemen, 2019)
Nowadays the business world should be able to operate effectively and efficiently to create corporate excellence including operational excellence. The object of this research is the operating strategy and operational excellence. The purpose of this research is to measure and determine how much influence the operation strategy for operational excellence in SME Food and Beverages in Bandung regency. The sample in this study was 100 respondents. The sampling method is nonprobability sampling with accidental sampling. Based on the discussion of the data concluded that the effect of operating strategies provide 58.6% of the operational excellence of the SME Food and Beverages in Bandung regency.